Novel flavonoid C-8 hydroxylase from Rhodotorula glutinis: identification, characterization and substrate scope - Kinga Dulak; Sandra Sordon; Agata Matera; Bartosz Kozak; Ewa Huszcza; Jarosław Popłoński (Microbial Cell Factories, 2022)
Abstract Background The regioselective hydroxylation of phenolic compounds, especially flavonoids, is still a bottleneck of classical organic chemistry that could be solved using enzymes with high activity and specificity. Yeast Rhodotorula glutinis KCh735 in known to catalyze the C-8 hydroxylation of flavones and flavanones. The enzyme F8H (flavonoid C8-hydroxylase) is involved in the reaction, but the specific gene has not yet been identified. In this work, we present identification, heterologous expression and characterization of the first F8H ortho-hydroxylase from yeast. Results Differential transcriptome analysis and homology to bacterial monooxygenases, including also a FAD-dependent motif and a GD motif characteristic for flavin-dependent monooxygenases, provided a set of coding sequences among which RgF8H was identified. Phylogenetic analysis suggests that RgF8H is a member of the flavin monooxygenase group active on flavonoid substrates. Analysis of recombinant protein showed that the enzyme catalyzes the C8-hydroxylation of naringenin, hesperetin, eriodyctiol, pinocembrin, apigenin, luteolin, chrysin, diosmetin and 7,4ʹ-dihydroxyflavone. The presence of the C7-OH group is necessary for enzymatic activity indicating ortho-hydroxylation mechanism. The enzyme requires the NADPH coenzyme for regeneration prosthetic group, displays very low hydroxyperoxyflavin decupling rate, and addition of FAD significantly increases its activity. Conclusions This study presents identification of the first yeast hydroxylase responsible for regioselective C8-hydroxylation of flavonoids (F8H). The enzyme was biochemically characterized and applied in in vitro cascade with Bacillus megaterium glucose dehydrogenase reactions. High in vivo activity in Escherichia coli enable further synthetic biology application towards production of rare highly antioxidant compounds.